Relationship Between Dispositional Mindfulness and Living Condition and the Well-Being of First-Year University Students in Japan - Irie, Tomonari; Yokomitsu, Kengo (Frontiers in Psychology, 2019)
The present study was conducted to examine how dispositional mindfulness and living conditions are related to well-being among first-year university students in Japan. Participants were 262 Japanese first-year students (156 females and 106 males; Mage = 18.77 years, SDage = 0.85). Dispositional mindfulness was measured using the Mindful Attention Awareness Scale, and living condition was operationalized as living at home or living alone after having left their home. Hierarchical multivariate regression analysis was used to analyze whether the factors of living condition and dispositional mindfulness had predictive effects on well-being. The results showed that dispositional mindfulness had a positive effect on well-being in first-year university students; however, living condition had no significant effect. On the other hand, the interaction between living condition and dispositional mindfulness had a significant effect on well-being. Simple slope analysis revealed that higher levels of dispositional mindfulness had a protective effect in the relationship between living condition and well-being. These results suggest that an intervention to promote dispositional mindfulness could be effective in protecting the well-being of first-year university students, especially for first-year university students who have left their home and are living alone. Further research will be necessary to examine longitudinally how mental health changes depending on the level of dispositional mindfulness of first-year university students.